Hubungan Faktor Reinforcing Dengan Perilaku Seks Pranikah Remaja Desa Tinakin Laut Kabupaten Banggai Laut Provinsi Sulawesi Tengah (Window of Public Health Journal, 2025)
Premarital sexual behavior is any behavior that is driven by sexual desire either with the opposite sex or the same sex starting from behavior that is done with touch. This study aims to determine the Relationship between Reinforcing Factors and Premarital Sexual Behavior in Adolescents in Tinakin Laut Village, Banggai Laut Regency, Central Sulawesi Province in 2022. This type of research uses unique and rigorous quantitative research with a cross-sectional approach design. The population in this study were all adolescents in Tinakin Laut Village, totaling 221 adolescents. The sampling technique used Nonprobality sampling with purposive sampling calculations by selecting samples from the population. using data analysis methods of univariate analysis and bivariate analysis with the chi-square test at a peer role level of 93% (α = 0.05). The results showed that there was no relationship between peer roles and reinforcing factors with premarital sexual behavior in adolescents in Tinakin Laut Village, Banggai Laut Regency, Central Sulawesi Province in 2022 with a ρ value of 1,000. There is a relationship between the role of social media with Reinforcing Factors with premarital sexual behavior in adolescents in Tinakin Laut Village, Banggai Laut Regency, Central Sulawesi Province in 2022 with a ρ value of 0.024. There is a relationship between the promotion of the role of sexual education with Reinforcing Factors of Premarital Sexual Behavior in Adolescents in Tinakin Laut Village, Banggai Laut Regency, Central Sulawesi Province in 2022 with a ρ value of 0.017, There is no relationship between the role of parents with Reinforcing Factors of Premarital Sexual Behavior in Adolescents in Tinakin Laut Village, Banggai Laut Regency, Central Sulawesi Province in 2022 with a ρ value of 0.126.